Engineering a conduction-consistent cardiac patch with rGO/PLCL electrospun nanofibrous membranes and human iPSC-derived cardiomyocytes - Tan, Yao; Chen, Ying; Lu, Tingting; Witman, Nevin; Yan, Bingqian; Gong, Yiqi; Ai, Xuefeng; Yang, Li; Liu, Minglu; Luo, Runjiao; Wang, Huijing; Ministrini, Stefano; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The healthy human heart has special directional arrangement of cardiomyocytes and a unique electrical conduction system, which is critical for the maintenance of effective contractions. So precise arrangement of cardiomyocytes and conduction consistency of vitro cardiac models is very important. Here, we prepared aligned electrospun rGO/PLCL membranes using electrospinning technology to mimic the natural heart structure. The physical, chemical and biocompatible properties of the membranes is tested. Then, hiPSC-CMs were assembled on electrospun rGO/PLCL membranes to construct a myocardial muscle patch and the conduction consistency of cardiomyocytes were carefully recorded. We found that electrospun rGO/PLCL fibers presented with an ordered and arranged structure, excellent mechanical properties, oxidation resistance and effective guidance of 3T3 cells and hiPSC-CMs. The addition of rGO can be beneficial for maturation and synchronous electrical conductivity of hiPSC-CMs in this cardiac patch. This study verified the possibility of using this conduction-consistent cardiac patch to enhance drug screening and disease modeling applications. Implementation of such a system could one day lead to in vivo cardiac repair applications.